2022
DOI: 10.1186/s13020-022-00698-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating network pharmacology, UPLC-Q–TOF–MS and molecular docking to investigate the effect and mechanism of Chuanxiong Renshen decoction against Alzheimer's disease

Abstract: Background and aim Chuanxiong Renshen decoction (CRD) is a traditional Chinese medicine compound used to treat Alzheimer's disease (AD). However, the effects and active ingredients of CRD and its mechanism have not been clarified. We aimed to determine the neuroprotective effects of CRD in a triple-transgenic mouse model of AD (3 × Tg-AD) and investigate the possible active ingredients and their mechanisms. Methods Morris water maze (MWM) tests wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…All the isolated alkaloids were also evaluated for AChE inhibitory activities by the Ellman method using donepezil as a positive control. 30–32 Compound 2 (IC 50 2.54 μM) revealed remarkable AChE inhibitory activity compared to donepezil (IC 50 3.49 μM), and others have no obvious activity. To further investigate the interactions of compound 2 with AChE, molecular docking was performed.…”
Section: Resultsmentioning
confidence: 99%
“…All the isolated alkaloids were also evaluated for AChE inhibitory activities by the Ellman method using donepezil as a positive control. 30–32 Compound 2 (IC 50 2.54 μM) revealed remarkable AChE inhibitory activity compared to donepezil (IC 50 3.49 μM), and others have no obvious activity. To further investigate the interactions of compound 2 with AChE, molecular docking was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The 76 overlapping components and disease targets of DJZD for the treatment of POI were imported into the STRING database to construct the PPI network 34 . The conditions were set as follows: The species was set to “ Homo sapiens ,” 35 the required score was set to “medium confidence (0.400),” 36 the nodes disconnected from the network were hidden, and other parameters were kept as default 25 . The protein–protein network (Figure 4B) contains 75 nodes and 950 edges.…”
Section: Resultsmentioning
confidence: 99%
“…Shen et al 33 applied network pharmacology to explore the action targets, pathways, and mechanisms of Chuanxiong Renshen Decoction (CRD) in the treatment of AD. The study first identified the main effective components of CRD using mass spectrometry analysis, retrieved potential targets of CRD components from the SwissTargetPrediction database, and screened AD-related targets from the Disgenet and Genacards databases.…”
Section: The Application Of Bioinformatics In Drug Research For Alzhe...mentioning
confidence: 99%